The implantable cardioverter-defibrillator: postcode prescribing in the UK 1998–2002. Issue 10 (29th March 2005) - Cunningham, A D; Plummer, C J; McComb, J M; Lord, S W; Cunningham, M W; Toussaint, J-M; Rickards, A F
Abstract : Objective: To determine the rate of implantable cardioverter-defibrillator (ICD) implantation across the UK during the period 1998 to 2002. Design: Observational self reporting with cross checking. Setting: All ICD implanting centres coordinated by the National Pacemaker and ICD Database. Patients: Every patient receiving an ICD in the UK from 1998 to 2002. Main outcome measures: Date of implantation and postcode of each ICD recipient during the study period. Results: ICD implantation increased in the UK in the five year period studied but fell far short of the European average and national targets. Implantation rates varied greatly by region. Conclusions: The low rate of ICD implantation in the UK and the disparity between regions require further study to determine the barriers to this evidence based treatment.